2005
DOI: 10.1002/elps.200500462
|View full text |Cite
|
Sign up to set email alerts
|

Titanium dioxide nanoparticles-coated column for capillary electrochromatographic separation of oligopeptides

Abstract: A novel column made through the condensation reaction of TiO2 nanoparticles (TiO2 NPs) with silanol groups of the fused-silica capillary is described. EOF measurements under various buffer constitutions were used to monitor the completion of reactions. The results indicated that the EOF was dependent on the interactions between buffers and the bonded TiO2 NPs. With formate/Tris buffer, EOF reversal at pH below 5 and cathodic EOF at pH above 5 were indicated. The pI of the bonded TiO2 NPs was found at approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
1
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 42 publications
0
42
1
1
Order By: Relevance
“…Hsieh et al [8] used titanium dioxide nanoparticles to coat the inside of fused-silica capillaries. The covalently bonded TiO 2 exhibited a pI at pH < 5, so that a reversal of the direction of the EOF was observed at this pH.…”
Section: Amino Acids and Peptidesmentioning
confidence: 99%
“…Hsieh et al [8] used titanium dioxide nanoparticles to coat the inside of fused-silica capillaries. The covalently bonded TiO 2 exhibited a pI at pH < 5, so that a reversal of the direction of the EOF was observed at this pH.…”
Section: Amino Acids and Peptidesmentioning
confidence: 99%
“…Hsieh et al [28,29] reported that the TiO 2 NP-coated capillary would exhibit exceptional surface properties which are depending on buffer composition and pH. In order to study the effect of TiO 2 NPs upon EOF, phenylmethanol was used as the neutral EOF marker.…”
Section: Effect Of Tio 2 Nps On Eofmentioning
confidence: 99%
“…Fujimoto [27] demonstrated that titanium dioxide-coated capillaries can be used for the CE and CEC separation of carbohydrates and proteins. Hsieh et al [28] were the first to prepare TiO 2 NP-coated capillaries for the open-tubular CEC separation of oligopeptides. Next, this group attempted to use TiO 2 NP-coated columns for the CEC separation of proteins of similar molecular weight or pI's for further applicability evaluation [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have prepared TiO 2 NP-coated capillaries for the open-tubular CEC separation of oligopeptides [30]. The surface properties of the prepared columns are significantly affected by the composition of the mobile phase, and are therefore very attractive for our purpose.…”
Section: Introductionmentioning
confidence: 99%